Intentional avermectin pesticide ingestion: a retrospective multicenter study. (3rd October 2022) - Wu, Yi-Kan; Chang, Chia-Hau; Yu, Jiun-Hao; Lan, Kai-Ping; Yen, Tzung-Hai; Chang, Shu-Sen; Seak, Chen-June; Chang, Hsing-Yuan; Chen, Hsien-Yi
Abstract: Context: Avermectin pesticides are widely used in agriculture, and are thought to have low toxicity in humans. However, information on their toxicity after accidental or deliberate ingestion is limited. Objective: The aim of this study was to evaluate the clinical manifestations of avermectin pesticide ingestion and identify factors associated with severe outcomes (death, intubation, or sustained hypotension requiring inotrope therapy). Materials and Methods: This multicenter retrospective study included patients who visited the emergency departments of six teaching hospitals due to acute avermectin pesticide ingestion between January 2012 and May 2020. Patients who reported ingestion of any other pesticides, drugs, or substances were excluded. Results: In total, 64 patients (median age, 72 years) were included: 60 had ingested emamectin pesticides, and 4 had ingested abamectin. Almost all (98%) were cases of self-harm. The most common presentation was drowsiness (47%), with a median Glasgow Coma Scale (GCS) score of 14, followed by shortness of breath (SOB)/dyspnea (33%) and nausea/vomiting (22%). Concurrent methanol exposure ( via the solvent) was confirmed or suspected in five patients. Seventeen patients (27%) were intubated. Three patients who developed respiratory failure were not intubated because of a "do-not-resuscitate" (DNR) order. Four patients developed sustained hypotension requiring inotrope therapy. Fifty patients (78%) were admitted, of whom 27 (42%) required intensive care unit (ICU) admission. Four patients died, three of whom had a DNR order. Based on our definition, 20 patients (31%) had severe outcomes. A multivariate logistic regression model showed that a GCS score < 13 (OR 68.1, 95% CI 3.8–999) and the presence of SOB/dyspnea (OR 50.2, 95% CI 3.0–849.9) were associated with severe outcomes. Conclusions: Most patients who intentionally ingested avermectin pesticides required inpatient treatment. Forty-two percent needed ICU care and 31% had severe outcomes. A GCS score < 13 and SOB/dyspnea were independently associated with severe outcomes.